2006
DOI: 10.1101/gr.4527806
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale identification of protein–protein interaction of Escherichia coli K-12

Abstract: Protein-protein interactions play key roles in protein function and the structural organization of a cell. A thorough description of these interactions should facilitate elucidation of cellular activities, targeted-drug design, and whole cell engineering. A large-scale comprehensive pull-down assay was performed using a His-tagged Escherichia coli ORF clone library. Of 4339 bait proteins tested, partners were found for 2667, including 779 of unknown function. Proteins copurifying with hexahistidine-tagged bait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
424
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 377 publications
(447 citation statements)
references
References 41 publications
22
424
0
1
Order By: Relevance
“…As expected, proteins with a higher degree had a higher RIP. We repeated the analysis with three large PPI datasets (13)(14)(15) that used different stringency cutoffs, and found no significant difference in this trend in any of these datasets.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, proteins with a higher degree had a higher RIP. We repeated the analysis with three large PPI datasets (13)(14)(15) that used different stringency cutoffs, and found no significant difference in this trend in any of these datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Interacts with FdhD-To ascertain the interaction of IscS with FdhD reported by large-scale studies (7,8), bacterial two-hybrid experiments were conducted (Fig. 1A).…”
Section: Iscs Specificallymentioning
confidence: 99%
“…TusA participates in a pathway that modifies tRNA, and IscU is a so-called [Fe-S] scaffold protein. In addition to TusA and IscU, large-scale interactome studies identified FdhD as a binding partner of IscS (7,8). FdhD has been shown to be required for the activity of formate dehydrogenases (FDHs) 2 in E. coli through an unknown mechanism (9,10).…”
mentioning
confidence: 99%
“…This complex may constitute a sulfate assimilation metabolon (Shibagaki 2007), deletion or mutation of which increases resistance to selenate toxicity (El Kassis et al 2007). Interestingly, E. coli CysA also can bind to OASTLa/CysK (Arifuzzaman et al 2006). STAS domains in plant SulP and mammalian SLC26 transporters are essential for plasma membrane targeting and for transport function.…”
Section: Role Of the Stas Domain In Rv1739c Functionmentioning
confidence: 99%